La dimensión cognitiva de la compasión y la vida moral: una indagación sobre los fundamentos de la teoría de las emociones de Martha Nussbaum (2019)
This research is a critical approach to Martha Nussbaum's thinking about the cognitive dimension of compassion. The thesis fundamentally exposes a plausible approach that clarifies and complements various plot voids that are identified in their cognitive-evaluating vision of emotions. In particular, the notion of cognition is problematized, and a philosophical and interdisciplinary explanation is offered that makes it possible to understand the nature of complex moral emotions, such as compassion, based on a classification of emotions according to the level of cognitive complexity that possess the organisms in which they express themselves. If we argue that the cognitive operates in every organism that has information selection processes, and if we defend the idea that the level of cognitive complexity present in each species determines the appearance or absence of particular emotional states, then we can distinguish between basic emotions, which we share with nonhuman animals, of complex emotions that are characteristic of our greater cognitive development. This approach contributes to the clarification of how cognitive processes are essential to our emotions, and is supported from an alternative view why compassion, understood as a complex moral emotion, can also be considered a public emotion that uniquely captures the experience of human vulnerability, and generates the citizen commitments that are essential to sustain the ideals of social justice and respect for human dignity that guarantee democratic stability in the present and future of humanity.